The assessment of time management skills in Chinese and Croatian students - Črnjar, Kristina (Array, 2019)
Time management is the ability of consciously deciding and controlling the amount of time spent on different activities in order to be more productive and effective. In order to achieve academic success, students should be able to manage a large number of activities, from going to lectures, studying, participating in extra-curricular activities, to making sure they are getting enough rest to stay healthy. The purpose of this research was to determine if there are any significant differences in the effective time management between Chinese and Croatian students. Even though the cultural differences between these two groups are substantial, both groups are becoming a part of the same education and business market. The research was conducted on the sample of 340 Chinese and Croatian students using an online survey. The results have shown that in several time management activities there are statistically significant differences between Chinese and Croatian students. The results also indicate that the Croatian respondents are better at setting goals, determining priorities and performing tasks by priority, while Chinese students delegate tasks and determine and eliminate time wasting activities more often than their Croatian counterparts do. On the other hand, Croatian students waste more time on activities such as conducting tasks of small importance and fun activities of no relevance (e.g. “surfing” the Internet, private telephone conversations, chatting, etc.), while Chinese students are in the forefront with regard to ineffective and supernumerary meetings and overly long and supernumerary phone conversations.